Advertisement Remove all ads

Show the X= -3 is a Solution of `X^2+6x+9=0` - Mathematics

Advertisement Remove all ads
Advertisement Remove all ads

Show the x= -3 is a solution of `x^2+6x+9=0`

Advertisement Remove all ads

Solution

The given equation is `x^2+6x+9=0` 

Putting `x=-3` in the given equation, we get  

`LHS=(-3)^2+6xx(-3)+9=9-18+9=0=RHS` 

∴` x=-3` is a solution of the given equation.  

Concept: Application of Quadratic Equation
  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

RS Aggarwal Secondary School Class 10 Maths
Chapter 10 Quadratic Equations
Q 33

Video TutorialsVIEW ALL [1]

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×